Cancer and Diverticulitis of the Sigmoid Colon. Differentiation with Computed Tomography Versus Magnetic Resonance Imaging: Preliminary Experiences. (April 2013) - Öistämö, Emma; Hjern, Fredrik; Blomqvist, Lennart; Von Heijne, Anders; Abraham-Nordling, Mirna
Background: Both colon cancer and diverticular disease are common in the Western world. A challenge when patients present with clinical findings is that both diseases can present with symptoms that may mimic the other. Purpose: To determine whether magnetic resonance imaging (MRI) could be helpful to differentiate between diverticulitis and cancer of the sigmoid colon compared to the differentiation offered by evaluation of multidetector computed tomography (CT) in a clinical situation. Material and Methods: Thirty patients were consecutively included. Fifteen patients were under work-up for a recently diagnosed sigmoid cancer and 15 patients had recently been treated in hospital due to first-time acute sigmoid diverticulitis. All patients underwent CT, T2-weighted MRI and diffusion-weighted MRI. Anonymized examinations were retrospectively presented in random order to one experienced radiologist. Results: With contrast-enhanced CT, the sensitivity and specificity for diagnosis of cancer and diverticulitis were 66.7% (10/15) and 93.3% (14/15), respectively. Using T2-weighted and diffusion-weighted MR images, the sensitivity and specificity for diagnosis of cancer and diverticulitis were 100% (14/14) and 100% (14/14), respectively. Conclusion: MRI provides information that may contribute to improve the differentiation between sigmoid cancer and diverticulitis that is offered by CT. These encouraging results need to be confirmed in a larger study.